Learning Empirical Legal Research Methods in Understanding Living Law in Society - Hana Krisnamurti; Erika Srie Mustika; Nelawati Nelawati; Rezky Muliamarta; Mikael Irfan Limbong; Muhammad Dwi Yuliandy (Civiliza Publishing, Indonesia., 2026)
In essence, law cannot be separated from social life, as it emerges, develops, and functions to regulate patterns of relationships between individuals within a social order. The concept of living law emerged, namely law that lives and develops through customs, traditions, and behavioral patterns recognized as guidelines for action. This study aims to analyze the role of empirical legal research methods in identifying and understanding living law in society. This research method uses a juridical-empirical approach by observing legal practices, social behavior, and the interaction between written legal norms and prevailing social norms. The results show that the empirical legal method enables an understanding of law as a dynamic social reality, while simultaneously revealing the gap between normative law and actual legal practice. This approach is also capable of identifying social, cultural, economic factors, and public legal awareness that influence the effectiveness of law. Thus, the empirical legal research method is a crucial instrument for the development of legal science, particularly in formulating legal policies that are responsive to societal needs and realities. Understanding living law through an empirical approach can encourage the creation of a legal system that is not only formally valid but also effective, relevant, and socially just.